Sedation Monitoring and Management during Percutaneous Endoscopic Lumbar Discectomy - Menekse Oksar; Tulin Gumus; Orhan Kanbak (Case Reports in Anesthesiology, 2016)
Percutaneous endoscopic laser discectomy (PELD) is a painful intervention that requires deep sedation and analgesia. However, sedation should be light at some point because cooperation by the patient during the procedure is required for successful surgical treatment. Light sedation poses a problem for endotracheal intubation, while patients placed in the prone position during percutaneous endoscopic discectomy pose a problem for airway management. Therefore, under these conditions, sedation should be not deeper than required. Here we report the sedation management of three cases that underwent PELD, with a focus on deep and safe sedation that was monitored using bispectral index score and observer’s assessment of alertness/sedation score.